Private environmental consultancy reveals five genera and ten species of angiosperms new to Rio Grande do Norte state, northeastern Brazil - Moura, Edweslley Otaviano de; de Sousa, Valdeci Fontes; Soares, Arthur de Souza; Versieux, Leonardo M. (Check list (Luís Felipe Toledo), 2018)
New occurrences of 10 species of angiosperms from Rio Grande do Norte state are reported. These data were collected by an environmental consultancy prior to the establishment of a wind farm. These records demonstrate the presence of knowledge gaps in the Caatinga flora of the state and show how an environmental consultancy can positively contribute towards the documentation of biodiversity in areas prior to their modification by human activities. In particular, at a time when the Brazilian Congress is discussing the elimination of environmental studies for licensing new developments, these new occurrence data highlight the importance of environmental studies.